STRATEGIC PLAN ANALYSIS USING THE BALANCED SCORECARD FRAMEWORK AT YOGYAKARTA ISLAMIC HOSPITAL PDHI - Prihatmoko, Cahyo; Kusbaryanto, Kusbaryanto; Hidayah, Nur (International Journal Labs, 2022)
Background: Personal protection equipment (PPE) is becoming more and more difficult to come by, which makes service management less and less effective. The expectation is that hospitals will be able to navigate this epidemic phase by converting all obstacles into assets and all chances into strengths. Thus, despite the current crisis and condition, the hospital can endure and possibly expand. Aim: The purpose of this study is to analyze the strategic plan using the BSC framework. Method: This research is qualitative research with a case study approach conducted at RSIY PDHI. This research design uses an approach to explore and understand the organization by presenting a comprehensive picture and reporting a detailed description of the source of information and setting it up without any intervention from the researcher. Findings: From a financial perspective, three strategic targets are set, namely revenue growth, cost reduction, and profitability improvement. From the customer's perspective, four strategic targets are set, namely, increasing the quality and quality of service, increasing customer satisfaction, increasing the quality of customer relationships, and improving the image of the hospital. From the perspective of internal business processes, three strategic targets are set, namely the integration of internal service processes, the improvement of the quality of the service process to customers, and the increasing speed of the service innovation process. From the growth and learning perspective, three strategic targets are set, namely increasing employee capabilities, increasing employee satisfaction, and increasing the use of integrated information systems.